Characteristics of Paediatric Patients Transported by Emergency Care Personnel in a Government Tertiary Care Centre, Mysuru, India: A Cross-sectional Study - K Nagendra; Girish Gopal; Sudha Rudrappa; D Karthick (JCDR Research and Publications Pvt. Ltd., 2022)
Introduction: Emergency Medical Service (EMS) systems have been well established and designed largely to cater to the needs of the cardiac and trauma related emergencies in adult patients. Paediatric emergencies are different; the benefits and outcomes of paediatric EMS have been assumed but without much evidence. With the emergence of paediatric and neonatal Advanced Life Support (ALS); it is imperative to have data that define the problems encountered in the prehospital care setting and also their outcome. This analysis may also provide insights into any modifications that may be required in the EMS system that exists to transport sick children. Aim: To characterise the paediatric prehospital care with emphasis on demography, presenting symptoms, treatment given, prehospital times, vitals monitoring and interventions done during EMS transport affiliated to Emergency Medical Service Agency. Materials and Methods: This descriptive cross-sectional study was conducted from July 2018 to June 2019 in Cheluvamba Hospital, a tertiary care referral teaching hospital attached to Mysore Medical College and Research Institute, Mysuru, India. The study included 147 children who were provided EMS by the 108 ambulance affiliated to the state/central government. Data pertaining to demography, presenting symptoms, vital sign monitoring, treatment given, various prehospital times, and interventions done during transport was obtained and analysed. Inpatient diagnosis with the duration of hospital stay and outcome in these childrens were also described. Results: Among the 147 children included; 3 were brought dead, hence the studied population comprised of 144 children. Amongst them, 42 were neonates and the remaining 102 belonged to the general paediatric population (older children). Overall, 61.8% were males and 57.64% hailed from a rural background. Mean 'onscene' time was 12.12±2.34 minutes and 5.50±5.01 minutes, and 'transport time' was 33.79±16.78 minutes, and 26.11±14.2 minutes for neonates and older children, respectively. Respiratory distress was the most common presenting symptom. The mean Heart Rate (HR, beats/min), Respiratory Rate (RR, cycles/min) and temperature (°C) in neonates was 129.86±27.91, 59.90±15.40 and 36.14±0.84 whereas in older children it was 112.81±28.39, 34.87±14.86, and 37.40±0.96, respectively. Mean systolic blood pressure (SBP mmHg) in children aged more than 10 years was 116.67±8.61. Of the 39 children aged more than 6 years, 36 (92.30%) had a Glasgow Coma Scale (GCS) between 13-15. The most common intervention done was administering oxygen in 84.02% (121/144) of children; 34.02% (49/144) of children were unstable at admission; 127 (88.2%) were discharged; remaining 17 (11.8%) succumbed to their illness. Onscene time of more than 15 minutes, transport time of more than 30 minutes and factors such as hypoxia, respiratory failure and shock at admission were significantly associated with mortality (p<0.001). Conclusion: Majority of the EMS transports were related to medical conditions. Basic Life Support (BLS) interventions were done albeit mostly in older children. Emergency Medical Technicians (EMT)/paramedics delivering EMS need special training to orient themselves to the special needs of critically ill children and to improve their outcome.